Bio-orthogonally crosslinked hyaluronate-collagen hydrogel for suture-free corneal defect repair. (October 2020) - Chen, Fang; Le, Peter; Fernandes-Cunha, Gabriella M.; Heilshorn, Sarah C.; Myung, David
Abstract: Biomaterials that mimic corneal stroma could decrease the need for donor corneal tissue and could decrease the prevalence of complications associated with corneal transplantation, including infection and rejection. We developed a bio-orthogonally crosslinked hyaluronate-collagen hydrogel which can fill corneal defects in situ without the need for any sutures, initiators, or catalysts. We studied the effects of biorthogonal crosslinking on the light transmittance of the hydrogel, which was greater than 97% water. The transmittance of the optimized hydrogel in the visible light range was over 94%. We also investigated the mechanical properties, refractive index, morphology, biocompatibility, and corneal re-epithelialization capacity of the hyaluronate-collagen hydrogel. Our in vitro, in vivo, and ex vivo results demonstrated that this bio-orthogonally crosslinked hyaluronate-collagen hydrogel has excellent potential as a biomaterial for cornea repair and regeneration.